ANALISIS PEMBERDAYAAN PEREMPUAN DALAM BIDANG USAHA EKONOMI MIKRO DI KABUPATEN TEMANGGUNG - Dyah Retno Arini; Priyastiwi Priyastiwi (Jurnal Riset Manajemen Akuntansi Indonesia, 2023)
The average role of women as professionals, especially in Temanggung Regency, is still below 50%. This shows that women access to economic development is still limited. Most of the women are still active in the informal sector and jobs that do not use sophisticated equipment and technology. Thus, even though women have participated in the workforce, because they do not have access and market opportunities, women have not been able to compete with men and with other businesses. The purpose of this study is to identify obstacles and obstacles in efforts to increase the role of women in economic development and to formulate government efforts to increase the role of women in economic development. This study uses a qualitative descriptive research method. The research instrument used observation and interview methods. There are several obstacles and constraints found by researchers. Obstacles in empowering women in the field of micro-economic enterprises are problems with funding, access to product marketing, human resources, and synergy between regional apparatuses. In addition, obstacles were found that came from internal micro business actors, namely willingness, entrepreneurial insight, and nature as a woman. Efforts that can be made by the government are strengthening women economic productivity, playing a role in developing business marketing networks, taking part in forming business forums/associations, providing assistance and coaching.